Efficacy and safety of radiofrequency catheter ablation in younger children with ventricular arrhythmias - Dong, Ziyan; Zhen, Zhen; Yu, Xia; Cui, Lang; Shao, Wei; Lin, Li; Gao, Lu; Yuan, Yue (Frontiers in Pediatrics, 2025)
Background and AimsTo compare the clinical characteristics of ventricular arrhythmias (VAs) in younger vs. older children, and to explore the safety and efficacy of radiofrequency catheter ablation (RFCA) in the treatment of VAs in young children.MethodsGeneral data, surgical data, and prognosis of all children with VAs who underwent RFCA at our hospital between 1 January 2005 and 31 December 2022 were retrospectively analysed. Patients were divided into two groups according to age: younger (<4 years); and older (≥4 years).ResultsData from 762 children with VAs were analysed, including 96 younger children (3.47 ± 0.75 years, 16.74 ± 3.98 kg) and 666 older children (9.44 ± 2.86 years, 38.85 ± 15.11 kg). Compared with the older group, there were more premature ventricular beats with ventricular tachycardia, earlier surgery, and more ablations under x-ray fluoroscopy in the younger group. The right ventricular outflow tract was the most common arrhythmia focus in both groups, followed by the tricuspid annulus in the younger group and the left ventricular septum in the older group. The acute success rates for younger and older children were 99.0% and 98.6%, respectively. The recurrence and complication rates in the two groups were similar, and there was no significant difference in radiation dose.ConclusionsThe safety and efficacy of RFCA in the treatment of younger children with VAs were similar to those of older children. RFCA appears to be a viable therapeutic option for young children with drug-resistant VAs.